2021
DOI: 10.1016/j.chemgeo.2021.120456
|View full text |Cite
|
Sign up to set email alerts
|

In situ quantification of the nitrogen content of olivine-hosted melt inclusions from Klyuchevskoy volcano (Kamchatka): Implications for nitrogen recycling at subduction zones

Abstract: Assessing the N content of arc magmas and their mantle source remains a challenge because the volatile element composition of melts and gases can be modified during magma ascent, storage, and eruption. Given that melt inclusions (MIs) in Mg-rich olivine represent the best proxies for primary arc melts, we applied, for the first time, an in situ high-resolution secondary ion mass spectrometry (SIMS) method to determine the N concentration in olivine-hosted MIs from Klyuchevskoy volcano in Kamchatka. To reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 109 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…Given the paucity of data, the influence of subduction on the N budget of mantle plumes remains unclear. Nitrogen in arc mantle sources is also important to study, as it is likely influenced by recycled surface-derived components (Fischer et al, 2002;Füri et al, 2021;Taran, 2009). Sub-arc nitrogen may be especially well suited for placing constraints on N isotope signatures that may be transferred to the deep Earth.…”
mentioning
confidence: 99%
“…Given the paucity of data, the influence of subduction on the N budget of mantle plumes remains unclear. Nitrogen in arc mantle sources is also important to study, as it is likely influenced by recycled surface-derived components (Fischer et al, 2002;Füri et al, 2021;Taran, 2009). Sub-arc nitrogen may be especially well suited for placing constraints on N isotope signatures that may be transferred to the deep Earth.…”
mentioning
confidence: 99%
“…6 to fit the data. Taking [TiO2] = 0.4 wt% for recycled components (Kelley et al, 2003;Plank and Langmuir, 1998), it results that [N]slabs ~ 0.1 ppm N. A [N]slabs ~ 0.1 ppm N is not unreasonable: it is lower than N concentrations in the altered oceanic crust, consistent with ≥ 90% nitrogen losses from the slabs -likely occurring underneath sub-arc mantle sources (Füri et al, 2021;Labidi et al, 2021). The addition of 10 to 20% slabs (with [TiO2]slabs = 0.4 wt% and K2O/TiO2 = 0.5) to a depleted mantle (with [TiO2]depleted mantle = 0.13 wt% and K2O/TiO2 = 0.02) returns K2O/TiO2 ratios between 0.12 and 0.19, covering most of the enriched-MORB range (Fig.…”
Section: Scenario 2: Slabs Have Low N Concentrationsmentioning
confidence: 98%
“…Under higher temperatures relevant to hot subduction zones, laboratory experiments show a reversal of the nitrogen partition coefficient, such that slab-nitrogen would be quantitatively lost during devolatilization and mineral breakdown (Jackson et al, 2021). Füri et al, (2021) andLabidi et al, (2021) showed that the mantle wedges of two distinct subduction zones are enriched in N by ~ 1 to 2 orders of magnitude relative to the average MORB mantle. In the case of the Central American hot subduction zone, the N enrichment in the mantle wedge is indicative of near-quantitative nitrogen losses from the slab (Labidi et al, 2021).…”
Section: Revisiting the Deep N Cyclementioning
confidence: 99%